2021
DOI: 10.1101/2021.09.17.21263726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Dose SARS-CoV-2 Vaccination With BNT162b2 and AZD1222 Induce Disparate Th1 Responses and IgA Production

Abstract: While vaccination programs against SARS-CoV-2 are globally ongoing, disparate strategies for the deployment of spike antigen show varying effectiveness. In order to explore this phenomenon, we sought to compare the early immune responses against AZD1222 and BNT162b2. SARS-CoV-2 seronegative participants received a single dose of either vaccine and were analyzed for immune cell, effector T cell and antibody dynamics. AZD1222 induced transient leukopenia and major changes among innate and adaptive subpopulations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…When two mRNA vaccines, mRNA-1273 and BNT162b2, were compared, two doses of mRNA-1273 induced higher antibody titers (GMT, 3,836 U/mL) as compared to two doses of BNT162b2 (GMT of 1,444 U/mL). 35 There might also be differences in the type of antibody responses as BNT162b2 and AZ1222 both elicited IgM and IgG, 44 BNT162b2 vaccine was reported to induce much evident IgA responses. 45 , 46 In addition, although AZ1222 vaccine elicited lower antibody responses as our data showed, it has been shown that it induces more stable antibody responses over time.…”
Section: Discussionmentioning
confidence: 99%
“…When two mRNA vaccines, mRNA-1273 and BNT162b2, were compared, two doses of mRNA-1273 induced higher antibody titers (GMT, 3,836 U/mL) as compared to two doses of BNT162b2 (GMT of 1,444 U/mL). 35 There might also be differences in the type of antibody responses as BNT162b2 and AZ1222 both elicited IgM and IgG, 44 BNT162b2 vaccine was reported to induce much evident IgA responses. 45 , 46 In addition, although AZ1222 vaccine elicited lower antibody responses as our data showed, it has been shown that it induces more stable antibody responses over time.…”
Section: Discussionmentioning
confidence: 99%